Co-simulation of cyber-physical systems using a DEVS wrapping strategy in the MECSYCO middleware. (December 2018) - Camus, Benjamin; Paris, Thomas; Vaubourg, Julien; Presse, Yannick; Bourjot, Christine; Ciarletta, Laurent; Chevrier, Vincent
Most modeling and simulation (M&S) questions about cyber-physical systems (CPSs) require expert skills belonging to different scientific fields. The challenges are then to integrate each domain's tools (formalism and simulation software) within the rigorous framework of M&S process. To answer this issue, we give the specifications of the Multi-agent Environment for Complex-SYstem CO-simulation (MECSYCO) middleware which enables to interconnect several pre-existing and heterogeneous M&S tools, so they can simulate a whole CPS together. The middleware performs the co-simulation in a parallel, decentralized, and distributable fashion thanks to its modular multi-agent architecture. In order to rigorously integrate tools that use different formalisms, the co-simulation engine of MECSYCO is based on the discrete event system specification (DEVS). The central idea of MECSYCO is to use a DEVS wrapping strategy to integrate each tool into the middleware. Thus, heterogeneous tools can be homogeneously co-simulated in the form of a DEVS system. By using DEVS, MECSYCO benefits from the numerous scientific works which have demonstrated the integrative power of this formalism and give crucial guidelines to rigorously design wrappers. We demonstrate that our discrete framework can integrate a vast amount of continuous M&S tools by wrapping the Functional Mockup Interface (FMI) standard. To this end, we take advantage of DEVS efforts of the literature (namely, the DEV&DESS hybrid formalism and Quantized State System (QSS) solvers) to design DEVS wrappers for Functional Mockup Unit (FMU) components. As a side-effect, this wrapping is not restricted to MECSYCO but can be applied in any DEVS-based platform. We evaluate MECSYCO with the proof of concept of a smart heating use case, where we co-simulate non-DEVS-centric M&S tools.